An in-vitro study on the proliferative potential of rat bone marrow stem cells on electrospun fibrous polycaprolactone scaffolds containing micro-hydroxyapatite particles. (8th December 2014) - Akram, H.; Azari, P.; Wan Abas, W. A. B.; Zain, N. M.; Gan, S. N.; Yahya, R.; Wong, C. S.; Pingguan-Murphy, B.
<x content-type="archive" xml:space="preserve">Abstract</x> Hydroxyapatite has a chemical composition that closely resembles the mineral phase of natural hard tissues, making it a good material for use as a bone scaffold. Previous studies have demonstrated that the use of electrospun nanofibres that contain synthetic hydroxyapatite aids in bone regeneration. In this study, composite scaffolds of polycaprolactone and bovine-derived hydroxyapatite were produced by mixing bovine-derived hydroxyapatite powder into polycaprolactone solution, followed by electrospinning. Field emission scanning electron microscopy images show that the scaffolds contained an interconnected spheroidal porous network. Four groups of scaffolds containing different weight percentages of bovine-derived hydroxyapatite (0, 10, 30 and 50%) were prepared. The scaffolds were characterised by infrared spectroscopy and field emission scanning electron microscopy which was used to observe cell attachment to the scaffolds as well.